Pengaruh Kerelasian Debitur dan Penyampaian Jasa terbadap Citra Bank (Suatu Studi Pemberian Kredit UMK pada Debitur BankBRIKota Jambi) - Hapzi Hapzi (Jurnal Aplikasi Manajemen, 2010)
The purpose of this research is to develop the debitur response about the relation of UMKM debitur which done to BRI Jambi city to develop debitur response about credit service conveyed of UMKM which done by BRI Jambi and to know to the influence model of debitur balancing and the service conveying to BRI image in Jambi. The used of research method is the description survey me the de and explanatory survey, analysis unit in this research is the debiturs of BRI UMKM. With the sample size is 57 of UMKM Businessman based on the analysis result, that we know the debitur balancing which done by BRI in Jambi shown the seriousness of BRJ to get close with debitur to make active in pay their credit (retention), the frequency propose related with debitur to stay with the commitment or the debts by BRJ in Jambi although will be faced by attractive/the influence of competitor the frequency keeps the quality of credit and in order to the debitur still wants to propose the debt although the interest is higher than the others bank, the frequency keeps holding the contend of approve wits UMKM debitur with the rule, but doesn’t have more of trust/ to build or influence the debitur trust to the BRl of Jambi (trust worthiness), less to build the debitur trust to the honesty and integrity of BRI, but still to build the debit or trust of UMKM in the reputation of BRI Jambi, and to build the debitur trust in BRI Jambi to compare with another Bank in conveying UMKM credit service of BR1 Jambi, that is the credit propose of procedure, credit propose of requirement and debitur fund, warranty security of debitur, debitur private data privacy of security, the accurate of fund return with the approve before, the relation ship between BRI Jambi and debitur, but still less to keep the good relationship with the debitur that had been paid all the credit. The balancing of debitur and conveying of the service together will influence. The image of BRI Jambi, but if we can see in individual side, so the conveying of service is dominant to influence BRI image of Jambi.